Protection of Mitochondrial Potential and Activity by Oxyprenylated Phenylpropanoids - Francesco Epifano; Salvatore Genovese; Lucia Palumbo; Chiara Collevecchio; Serena Fiorito (Antioxidants, 2023)
A series of five naturally occurring oxyprenylated phenylpropanoids, namely, the coumarins auraptene (7-geranyloxycoumarin) 1 and 7-isopentenyloxycoumarin 2, and the coumaric acid and ferulic acid derivatives, 4’-isopentenyloxycoumaric acid 3, boropinic acid 4, and 4’-geranyloxyferulic acid 5 were tested for their effects on mitochondrial functionality using the organophosphate pesticides glyphosate and chlorpyrifos, and resveratrol, as the reference. While not showing an appreciable in vitro antioxidant activity, and virtually no or a little effect on the viability of non-cancer cell lines BEAS-2B and SHSY-5Y, all phytochemicals exhibited a marked protective effect on mitochondrial potential and activity, with values that were comparable to resveratrol. Auraptene 1 and 7-isopentenyloxycoumarin 2 were seen to be the most effective secondary metabolite to this concern, in particular in being able to completely abolish the decrease of mitochondrial potential induced by increasing concentration of both glyphosate and chlorpyrifos. All the compounds tested also exhibited a protective effect on mitochondrial activity. The potency displayed will shed more light on the molecular basis of the beneficial effects of auraptene, 7-isopentenyloxycoumarin, and structurally related oxyprenylated phenylpropanoids reported to date in the literature.